Práticas de textualização na escola: limites ou possibilidades? - Silva, Thatyana Angélica dos Santos (2008)
Recently, the textbook has taken up an important position about public politics of Brazilian education and it has been a matter of several researches in all the country. However, some criticism about the quality of this teaching material is done by several studious people. This research has the purpose to analyze the use which the teacher makes of the proposal of text production of Portuguese textbook of third grade of fundamental teaching and production conditions that are provided for the students. We analyzed five textbooks, the most used textbooks in Maceio and we observed five teacher s text practice of Municipal Teaching. Therefore, considering fundamentals practiced by National Curriculum Standard which advises about writing process, we realized the teacher s practical way contributes to educate competent writers at school. Referring to textbook use, the proposals about text production developed from this material are rare and, when they are made, they are connected with a traditional practice which not favors the handy writer s formation with written language. The teacher develops activities which not value interretional character. The texts are produced without any purpose. Furthermore, the opportunities which the students find to produce texts, from a Portuguese textbook or not, are not enough to comprehend the complex task of producing texts.